Comparative effects of flywheel and traditional resistance training on reactive strength and multidirectional COD in elite badminton players - Tan, S.; Lu, Z.; Yuan, S.; Zhang, Z.; Zou, X.; Zhang, M.; Zhang, L.; Li, S.; Dai, J. (Frontiers in Physiology, 2025)
Purpose: This study compared the effects of flywheel resistance training (FRT) versus traditional resistance training (TRT) on reactive strength, dynamic balance, and sport-specific change-of-direction (COD) ability in elite badminton players.